Penerapan Model Bisnis Syariah Dalam Pemberdayaan Petani di Kp. Pamulihan Ds. Ciporeat Kab. Bandung - Salam, Mochamad Fadlani; Khonsa, Balqis Rhatuna; Abdurrozak, Fahrul; Rafli, Alif Rayhan Abdurrahman; Pradia , Java (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Agriculture is one of the most important economic sectors in Kp. Pamulihan, Ciporeat Village, Bandung Regency. The majority of the local community depends on farming as their main source of income. However, farmers face a major challenge in the process of marketing their crops, namely the dominant role of middlemen who tend to be exploitative. The practice of purchasing agricultural products at low prices and the lack of transparency in transactions keep farmers' welfare low. This study aims to analyze the role of middlemen in the supply chain and evaluate the potential for implementing sharia-based business models as an alternative solution. The research method used a qualitative approach with a case study at the research location. Data collection techniques were conducted through in-depth interviews with 7 vegetable farmers, field observations, and focus group discussions (FGDs). The results showed that the distribution system that has been controlled by middlemen creates structural inequality that is detrimental to farmers. As an alternative, sharia business models such as mudharabah and musyarakah have great potential to increase farmers' independence and build a fairer distribution system. Recommendations from this study are the need for intensive Islamic economic education to farmers as well as synergy between Islamic financial institutions and farmer groups in the region.